2020
DOI: 10.1136/bmjopen-2020-037591
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation strategies in critical care for the treatment of atrial fibrillation: a protocol for a systematic review and meta-analysis

Abstract: IntroductionAtrial fibrillation (AF) is the most common cardiac arrhythmia in critically ill patients and is associated with an increased risk of thromboembolic events and mortality. Oral anticoagulation for thromboembolism prophylaxis is a key component of managing AF in the general population and is recommended by National Institute for Health and Care Excellence guidelines. However, assessment tools used to aid decision making about anticoagulation have not yet been validated in the critical care setting. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Mortality at 28 days and 90 days was not reported in any of the studies, therefore it was excluded from analysis. The protocol for this review outlined the intention to review the incidence of thromboembolic events, including stroke 25 , TIAs, mesenteric ischaemia, acute limb ischemia and pulmonary embolism. Only one study 29 reported the risk of arterial thromboembolism (including embolism or thrombosis in the extremities), whilst the other three studies reported stroke incidence only 15,21,28 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality at 28 days and 90 days was not reported in any of the studies, therefore it was excluded from analysis. The protocol for this review outlined the intention to review the incidence of thromboembolic events, including stroke 25 , TIAs, mesenteric ischaemia, acute limb ischemia and pulmonary embolism. Only one study 29 reported the risk of arterial thromboembolism (including embolism or thrombosis in the extremities), whilst the other three studies reported stroke incidence only 15,21,28 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…23,24 The protocol for this systematic review is registered with the International Prospective Register of Systematic Reviews (PROSPERO) database (registration number: CRD42020158237). A full publication of this protocol is available 25 (PMID: 33082186, doi:10.1136/ bmjopen-2020-037591).…”
Section: Protocol and Registrationmentioning
confidence: 99%
See 1 more Smart Citation